ANALYTICAL STUDY ON EMPLOYEE JOB SATISFACTION IN PIXELLOID COMPANY, HYDERABAD (International Journal of Food and Nutritional Sciences, 2022)
Job satisfaction as any combination of psychological, physiological and environmentalcircumstances that cause a person truthfully to say “I am satisfied with my job”